Osmolar relation between cerebrospinal fluid and serum in hyperosmolar hypernatraemic dehydration. Issue 9 (September 1976) - Habel, A H; Simpson, H
Abstract : The relation between cerebrospinal fluid (CSF) and serum osmolality was studied in 16 patients with hyperosmolar hypernatraemic dehydration before treatment. After correcting shock and acidosis, 0-45% saline in 2-5 or 5% dextrose was infused in each patient over a 48- to 72-hour period. During rehydration, serum osmolality, electrolyte concentrations, urea nitrogen, and blood pH were measured sequentially. Five patients developed severe neurological abnormalities within 48 hours of addmission (convulsions 2, convulsions with hemiplegia 2, hemiplegia 1). Of these, 3 had residual defects on follow-up at least one year later. This group was indistinguishable from the 11 without significant neurological abnormality, both on clinical grounds before rehydration, and after analysis of admission and subsequent serum biochemical variables. A significant osmolar gap (greater than 4 mmol/kg H2O) between serum and CSF was found in 13 patients. Severe neurological disturbance only occurred when CSF osmolality exceeded that of serum by 7 or more mmol/kg H2O. Discriminant analysis of the paired osmolar data showed that D = -117+1-74 X(CSF osmolality) -1-41 X (serum osmolality), and that severe neurological abnormality was predicted when D was positive.